The violence of the Lamb: martyrs as agents of divine judgement in the Book of Revelation - Middleton, Paul (Library of New Testament studies, 2018)
Cover -- Half title -- Title -- Copyright Page -- Contents -- Preface -- Abbreviations -- Introduction: Violence and Martyrdom in the Book of Revelation -- Reading the Violence of the Apocalypse -- Martyrdom in Revelation -- Plan of the Book -- Chapter 1 Christian 'Persecution' and the Dating of Revelation -- Introduction -- The Literary World of the Apocalypse -- Persecution and Suffering in Revelation -- The Imperial Cult in Revelation -- Social Reality and the Apocalypse -- Persecution and Suffering in the New Testament -- Persecution in Early Christian Writings -- The Emperor Cult -- The Image of the Beast: The Sacrifice Test -- Josephus -- Early Christianity -- Mark -- Q 12.2-9 -- Hebrews -- The Shepherd of Hermas -- 2 Timothy -- 1 John -- Conclusion -- Chapter 2 Not a Tame Lamb: Christology in the Apocalypse -- The Lion/Lamb Dichotomy -- The Lion -- The Lamb -- 'Standing as if Slain' (Revelation 5.6) -- Sacri cial Lamb -- Paschal Lamb -- Isaiah 53 -- Behold the 'Ram' of God -- The Lion/Lamb: Beyond Incongruity -- Chapter 3 The Lamb as Proto-Martyr -- The Revelation of Jesus Christ (Revelation 1-8) -- The Testimony of Jesus (Revelation 1.2) -- The First and the Last (Revelation 1.4) -- The Faithful Witness (Revelation 1.5-6) -- Coming on the Clouds (Revelation 1.7) -- Christophanies in the Apocalypse -- The Son of Man/Ancient of Days (Revelation 1.12-20) -- Christological Oracles (Revelation 2-3) -- The Rider on the White Horse (Revelation 19.11-16) -- The Lion and the Lamb (Revelation 4-5) -- Chapter 4 The Lamb as Divine Judge -- Violence and Judgement in the Apocalypse -- Judgment in the Oracles to the Seven Churches (Revelation 1-3) -- The Seven Seals and Trumpets (Revelation 6-7) -- The Sealed Scroll -- The First Four Seals (Revelation 6.1-8) -- The Sixth Seal: The Day of the Lord (Revelation 6.12-17)